Calcium/calmodulin-dependent protein kinase II (CaMKII) inhibition ameliorates arrhythmias elicited by junctin ablation under stress conditions - Tzimas, C.; Terrovitis, J.; Lehnart, S. E.; Kranias, EG; Sanoudou, D. (Heart RhythmHeart RhythmHeart Rhythm, 2015)
BACKGROUND: Aberrant calcium signaling is considered one of the key mechanisms contributing to arrhythmias, especially in the context of heart failure. In human heart failure, there is significant down-regulation of the sarcoplasmic reticulum (SR) protein junctin, and junctin deficiency in mice is associated with stress-induced arrhythmias. OBJECTIVE: The purpose of this study was to determine whether the increased SR Ca(2+) leak and arrhythmias associated with junctin ablation may be associated with increased calcium/calmodulin-dependent protein kinase II (CaMKII) activity and phosphorylation of the cardiac ryanodine receptor (RyR2) and whether pharmacologic inhibition of CaMKII activity may prevent these arrhythmias. METHODS: Using a combination of biochemical, cellular, and in vivo approaches, we tested the ability of KN-93 to reverse aberrant CaMKII phosphorylation of RyR2. Specifically, we performed protein phosphorylation analysis, in vitro cardiomyocyte contractility and Ca(2+) kinetics, and in vivo ECG analysis in junctin-deficient mice. RESULTS: In the absence of junctin, RyR2 channels displayed CaMKII-dependent hyperphosphorylation. Notably, CaMKII inhibition by KN-93 reduced the in vivo incidence of stress-induced ventricular tachycardia by 65% in junctin null mice. At the cardiomyocyte level, KN-93 reduced the percentage of junctin null cells exhibiting spontaneous Ca(2+) aftertransients and aftercontractions under stress conditions by 35% and 37%, respectively. At the molecular level, KN-93 blunted the CaMKII-mediated hyperphosphorylation of RyR2 and phospholamban under stress conditions. CONCLUSION: Our data suggest that CaMKII inhibition is effective in preventing arrhythmogenesis in the setting of junctin ablation through modulation of both SR Ca(2+) release and uptake. Thus, it merits further investigation as promising molecular therapy.
Tzimas, ChristosTerrovitis, JohnLehnart, Stephan EKranias, Evangelia GSanoudou, DespinaengR01 HL026057/HL/NHLBI NIH HHS/R01 HL064018/HL/NHLBI NIH HHS/HL26057/HL/NHLBI NIH HHS/HL64018/HL/NHLBI NIH HHS/Research Support, N.I.H., ExtramuralResearch Support, Non-U.S. Gov't2015/03/31 06:00Heart Rhythm. 2015 Jul;12(7):1599-610. doi: 10.1016/j.hrthm.2015.03.043. Epub 2015 Mar 23.
Keywords: *Arrhythmias, Cardiac/metabolism/prevention & control; Ablation Techniques; Animals; Benzylamines/*pharmacology; Calcium Signaling/*drug effects; Calcium-Binding Proteins/*metabolism; Calcium-Calmodulin-Dependent Protein Kinase Type 2/*metabolism; Calcium/*metabolism; Disease Models, Animal; Heart Failure/metabolism; Mice; Models, Cardiovascular; Myocytes, Cardiac/drug effects/metabolism; Phosphorylation/drug effects; Protein Kinase Inhibitors/pharmacology; Ryanodine Receptor Calcium Release Channel/metabolism; Sarcoplasmic Reticulum/drug effects/metabolism; Sulfonamides/*pharmacology